Indonesian Migrant Workers After Job Creation Law: A Challenging Problem for Protection Welfare - Suhartini, Endeh; Zaini, Mimi Fitriana; Widjojanto, Bambang; Yumarni, Ani (BESTUUR, 2023)
Job Creation Law has severely impacted the protection of foreign workers with changes to the Company Permit for Placement of Indonesian Migrant Workers (SIP3MI). This research aims to analyze changes to SIP3MI and its impact on the licensing mechanism for Indonesian migrant workers, which is related to the implementation of supervision of migrant workers as a juridical-administrative consequence of SIP3MI issuance. The research methodology used in this paper is a normative legal research method with a statue approach and conceptualization of legal protection, licensing, supervision, labour, and social justice to realize the protection of migrant workers when contracting and completing contracts. This research indicates an urgency for the government to protect migrant workers, seeing the increase in the number of migrant workers and complaints. The SIP3MI regulation, degrades the concept of protecting Indonesian migrant workers. The change in providing SIP3MI information from the relevant Ministry to the authority of the Central Government and being equated with Business Licensing thus changes the mechanism for issuing permits, which could severely impact the implementation of supervision and protection of Indonesian migrant workers. Therefore, the protection of migrant workers is no better than before the publication of the Omnibus Law. Legal certainty is needed to provide protection. Equating SIP3MI with business licensing is quite controversial and has the potential to create legal protection for migrant workers who are increasingly being pushed into a corner.